2002
DOI: 10.4148/1051-0834.2170
|View full text |Cite
|
Sign up to set email alerts
|

What’s the Impact with Congressional Aides? A Study of Communication Attitudes and Behaviors

Abstract: This article reports findings from an evaluation study of the USDA Science and Education Impact Fact Sheet Program. The program was established in 1995 to communicate tangible effects of USDAExtension programming to help maintain investment in land-grant and USDA research and educational programs. The single-page Impact Fact Sheets, which address such topics as agriculture and the environment, parenting, and waste management, have been distributed to stakeholders through mail and personal visits and distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…FBACT members subscribe to e-mail alerts containing legislative updates and a link to a Web page that would allow members to contact their legislators (Florida Farm Bureau, 2007). Previous research that indicates congressional aides seek agriculture-related information from interpersonal contacts within the agriculture and natural resources communities only after consulting government and internal sources, not agricultural media or land-grant institutions (Boone et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…FBACT members subscribe to e-mail alerts containing legislative updates and a link to a Web page that would allow members to contact their legislators (Florida Farm Bureau, 2007). Previous research that indicates congressional aides seek agriculture-related information from interpersonal contacts within the agriculture and natural resources communities only after consulting government and internal sources, not agricultural media or land-grant institutions (Boone et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Much of this research is increasingly conducted by nonacademic departments and applied communication units, mainly in attempts to improve editorial products, enhance customer service, or to show evidence of their worth or "impact" to the organization (Boone, Tucker & McClaskey, 2002;Tucker & Steel, 2003;Irani & Telg, 2001;Boone & Furbee, 1998;Wood-Turley & Tucker, 2003;Gerakis, 1997;Connors, Elliot & Heinze, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Richardson and his colleagues examined county-level government employees as a nontraditional audience for Extension and found that they did not rely on Extension information and preferred to receive information in printed form. Boone, Tucker, and McClaskey (2002) evaluated the effectiveness of United States Department of Agriculture (USDA) Impact Fact Sheets in communicating with congressional aides. They found less than half of the aides had seen or used the fact sheets.…”
Section: Introductionmentioning
confidence: 99%